Irrigation management for diversified cropping - International Irrigation Management Institute (International Irrigation Management Institute, 1987)
Improvements in rice growing technologies during the last two decades have resulted in a number of countries especially in the humid tropical regions of Asia, nearing self sufficiency in rice production. Consequently, policies are shifting in these countries toward minimizing the under-utilization of land by increasing the cropping intensity of irrigated areas, particularly by growing non-rice crops during the dry season. These workshop papers discuss the advantages of and constraints to crop diversification, in different country situations in Asia.